Effects of Augmented Reality-Based Digital Mobile Game-Based Learning on the Engagement of Students - Zhong Mengmeng; Han Xiao; Liu Xiangwei; Li Linying, (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Augmented reality, or AR, has become increasingly popular over the past ten years, particularly in education. Only a small number of publications, meanwhile, have thoroughly examined the research trends in the application of AR to mathematics education. Globally, two trends that are being implemented in education are AR and digital game-based mobile learning. It is still important to monitor the consequences of implementing both trends simultaneously in inclusive learning, though. We have created an inclusive AR video game to teach mathematical logic skills. To highlight the patterns in this study’s emphasis, eight themes were identified from the analysis of these literary works: learning challenges, testing strategies, benefits of AR for mathematics, different kinds of AR apps, tools for developing AR apps, research contribution categories, and math subtopics. Additionally, by providing researchers and educators with a synthesized review of learning mathematics through AR, this study may open up new research directions. Our study demonstrated that children with varying needs perform similarly when playing. The findings and the teaching staff’s input indicate that DGBL and AR should permit the inclusion of kids with disabilities in the instruction procedure.